PENGARUH MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP KEMAMPUAN MEMBACA CERPEN DIGITAL UNTUK KELAS VII PESERTA DIDIK - Wita Tri Indrayanti; Sujinah; Sulton Amin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of implementing the Cooperative Integrated Reading and Composition (CIRC) learning model on the ability to read digital short stories among students at SMP Muhammadiyah 7 Surabaya. This study was motivated by the low reading comprehension skills of students regarding digital short story texts, as well as the limited use of cooperative learning models that emphasize the integration of reading activities. This study employed a quantitative approach using a quasi-experimental method with a control group design. The research subjects consisted of two classes: an experimental class that implemented the CIRC learning model and a control class that used a conventional learning model. Data collection was conducted through a digital short story reading proficiency test, while data analysis utilized inferential statistical tests. The results indicated a significant effect of the CIRC learning model on students’ digital short story reading proficiency. Students who participated in learning using the CIRC model demonstrated higher proficiency in reading digital short stories compared to students who learned using a conventional learning model. Therefore, the CIRC learning model has proven effective in improving digital short story reading proficiency among students at SMP Muhammadiyah 7 Surabaya. This study was conducted to analyze the differences in results between the experimental group and the control group. This study employed a quantitative approach with a comparative design. The sample size consisted of 36 students from two classes: with 19 students in the control group and 17 in the experimental group. Since the sample size was less than 50, the Shapiro-Wilk test was performed on the pretest and posttest data, yielding a significance level (Sig.) of 0.0061 > 0.05 for the pretest data and 0.081 > 0.005 for the posttest data in the control group. Thus, it can be concluded that the data from both the control and experimental groups are normally distributed.